Penerapan Media Talking Stick Untuk Meningkatkan Keterampilan Berbicara Anak Usia Dini (Penelitian Tindakan Kelas Anak Kelompok B2 Di Tk Pertiwi 1 Kota Bengkulu) - Aaisyah Puspita Sari; M Nasirun; Anni Suprapti (Jurnal Ilmiah POTENSIA, 2017)
The purpose of this research was to improve children’s speaking skill by using talking stick media at B2 group of Kindergarten Pertiwi 1 in Bengkulu city. This research was a classroom action research (CAR), there’re 2 cycles, and each cycle consists of three meetings. The subject of the research was B2 group. There were 15 children consisted of 6 boys and 9 girls. The technique of collecting data in this research was done through observation and documentation, while in analyzing the data, the researcher used statistical technique with the average formula. The result of this research proved that talking stick media can improve early childhood’s speaking skill on the average number of 4.44 with good criteria. Based on the results of this study, can be done through the talking stick media.